Magnetic and thermal studies of Cu(II), Ni(II), Co(II) and Fe(II) complexes of ligands derived from 2-hydroxybenzaldehyde and polymethylenediamines / Afiq Azil - Afiq, Azil (2015)
The main objective of this research was to synthesise and characterise magnetic and thermally stable metal complexes, designed as functional molecular materials. The ligands (H2L1, H2L2, and H2L3) were Schiff bases prepared from 2-hydroxybenzaldehyde with 1,8-diaminooctane, 1,10-diaminodecane and 1,3-diaminopentane, respectively. The complexes were obtained from the reactions of these Schiff bases with [M(CH3(CH2)14COO)2], where M = Cu(II) (d9), Ni(II) (d8), Co(II) (d7) and Fe(II) (d6) ions. A total of 16 complexes were obtained by step-wise and/or one-pot reactions The Cu(II) complexes of H2L1 and H2L2 were mononuclear, but may exist as dimers. All iron complexes were dinuclear Fe(II), except [Fe(CH3(CH2)14COO)2(HL3)], which was a Fe(III) complex. All Co(II) complexes were octahedral, except [Co(L1)] which was square planar. Except for Ni(II) complexes of H2L1, and Ni(II) and Co(III) complexes of H2L2, which were diamagnetic, all other complexes were paramagnetic. All metal complexes of H2L1 and H2L2 were thermally stable (decomposition temperatures ranged from 205 °C to 320 °C). The thermal stability of metal complexes of H2L3 were lower than those of H2L1 and H2L2 (decomposition temperatures ranged from 142 °C to 209 °C). All of these complexes did not exhibit liquid crystal properties. The findings of this research were presented in one national and one international seminars, and published in one ISI journal.